Entrepreneurship in the Era of Artificial Intelligence: Redefining Opportunity Recognition, Labour Substitution, and Innovation Processes - Muhammad Sarfraz Latif; Mansoor Ahmed Soomro; Asif Ahmad; Muhammad Irfan Syed (Inverge Journal of Social Sciences, 2026)
This study examined the transformative role of artificial intelligence (AI) in entrepreneurship, focusing on opportunity recognition, labour substitution, and innovation processes. Rapid advancements in AI technologies altered traditional entrepreneurial practices by enabling data-driven decision-making, predictive analytics, and automation of routine tasks. Using a quantitative research design, data were collected from 350 entrepreneurs and managers of small and medium-sized enterprises (SMEs) who had adopted AI in their business operations. Descriptive statistics, reliability tests, regression analysis, and structural equation modelling (SEM) were employed to analyse the relationships between AI adoption and entrepreneurial outcomes. The results revealed that AI adoption significantly enhanced opportunity recognition by enabling entrepreneurs to identify emerging market trends, assess risks, and make informed strategic decisions. AI also facilitated labour substitution by automating repetitive tasks, allowing human resources to focus on creative and analytical roles. Moreover, AI-driven innovation processes accelerated product development, improved operational efficiency, and supported experimentation, thereby strengthening entrepreneurial performance. Despite these positive outcomes, challenges such as workforce displacement, ethical concerns, and limited access to AI technologies were identified as barriers to full adoption. The study concluded that AI functions as a strategic enabler that reshapes entrepreneurial practices, labour dynamics, and innovation strategies. The findings provide valuable insights for entrepreneurs, policymakers, and academic institutions to implement adaptive strategies for sustainable and inclusive entrepreneurial growth in the era of artificial intelligence. References Ali, A., & Rafiq-uz-Zaman, M. (2025). Institutional inertia vs. ethical innovation: A comparative analysis of AI governance at The Islamia University of Bahawalpur and Cambridge University Press. Contemporary Journal of Social Science Review, 3(4), 91–102. https://doi.org/10.63878/cjssr.v3i4.1695 Asif, M., Shahid, S., & Rafiq-uz-Zaman, M. (2025). Immersive technologies, awe, and the evolution of retail in the metaverse. International Premier Journal of Languages & Literature, 3(4), 713–748. https://ipjll.com/ipjll/index.php/journal/article/view/295 Audretsch, D. B., & Belitski, M. (2023). Artificial intelligence, entrepreneurship, and economic growth. Small Business Economics, 61(3), 1017–1035. https://doi.org/10.1007/s11187-022-00673-4 Badghish, M., & Soomro, T. R. (2024). Artificial intelligence and entrepreneurial innovation: Evidence from emerging markets. Technological Forecasting and Social Change, 191, 122450. https://doi.org/10.1016/j.techfore.2023.122450 Brynjolfsson, E., Rock, D., & Syverson, C. (2021). The productivity J-curve: How intangibles complement general purpose technologies. American Economic Journal: Macroeconomics, 13(1), 333–372. https://doi.org/10.1257/mac.20180345 Bughin, J., Hazan, E., Ramaswamy, S., Chui, M., Allas, T., Dahlström, P., Henke, N., & Trench, M. (2018). Artificial intelligence: The next digital frontier? McKinsey Global Institute. https://doi.org/10.2139/ssrn.3213930 Bui, T. H., & Duong, P. T. (2024). AI-enabled opportunity recognition: A study on startup decision-making. Journal of Business Research, 161, 113556. https://doi.org/10.1016/j.jbusres.2023.113556 Cockburn, I. M., Henderson, R., & Stern, S. (2019). The impact of artificial intelligence on innovation. NBER Working Paper, 24449. https://doi.org/10.3386/w24449 Dwivedi, Y. K., Hughes, L., Ismagilova, E., Aarts, G., Coombs, C., Crick, T., Duan, Y., Dwivedi, R., Edwards, J., Eirug, A., Galanos, V., Ilavarasan, P. V., Janssen, M., Jones, P., Kar, A. K., Kizgin, H., Kronemann, B., Lal, B., Lucini, B., … Williams, M. D. (2021). Artificial intelligence (AI): Multidisciplinary perspectives on emerging challenges, opportunities, and agenda for research. International Journal of Information Management, 57, 101994. https://doi.org/10.1016/j.ijinfomgt.2019.08.002 Fossen, F. M., McLemore, T., & Sorgner, A. (2024). Artificial intelligence and entrepreneurship. Foundations and Trends® in Entrepreneurship, 20(8), 781–904. https://doi.org/10.1561/0300000130 Haefner, N., Wincent, J., Parida, V., & Gassmann, O. (2021). Artificial intelligence and innovation management: A review, framework, and research agenda. Technological Forecasting and Social Change, 162, 120392. https://doi.org/10.1016/j.techfore.2020.120392 Jamil, R., Zhang, Y., Anwar, M., & Mustafa, S. (2025). Inclusive artificial intelligence in entrepreneurship: Access, adoption, and equity implications. Small Business Economics, 65(2), 1105–1124. https://doi.org/10.1007/s11187-024-00850-7 Kraus, S., Jones, P., Kailer, N., Weinmann, A., Chaparro-Banegas, N., & Roig-Tierno, N. (2022). Digital transformation: An overview of the current state of the art of research. Journal of Small Business Management, 60(1), 1–25. https://doi.org/10.1080/00472778.2020.1766690 Li, X., Wang, J., & Liu, X. (2022). Artificial intelligence capability and entrepreneurial opportunity recognition. Journal of Business Venturing Insights, 18, e00313. https://doi.org/10.1016/j.jbvi.2022.e00313 Machucho, J., & Ortiz, P. (2025). The role of artificial intelligence in entrepreneurial opportunity identification. Journal of Small Business Management, 63(1), 67–88. https://doi.org/10.1080/00472778.2023.2198765 Mariani, M. M., Perez-Vega, R., & Wirtz, J. (2023). Artificial intelligence and innovation: A systematic review and research agenda. Technovation, 120, 102528. https://doi.org/10.1016/j.technovation.2022.102528 Mikalef, P., Fjørtoft, S. O., & Torvatn, H. Y. (2024). Artificial intelligence-enabled dynamic capabilities and firm performance. Journal of Business Research, 168, 114101. https://doi.org/10.1016/j.jbusres.2023.114101 Obschonka, M., Audretsch, D. B., & Volkmann, C. (2020). Artificial intelligence and big data in entrepreneurship. Small Business Economics, 55(2), 339–351. https://doi.org/10.1007/s11187-019-00186-0 Omidmand, P., Dorri, R., Mozaffari, A., & Ataei, S. (2025). Artificial intelligence applications in lean startup methodology: A bibliometric analysis of research trends and future directions. Journal of Small Business and Entrepreneurship Development, 13(1), 45-67. Park, J.-H., Kim, S.-J., & Lee, S.-T. (2025). AI and creativity in entrepreneurship education: A systematic review of LLM applications. AI, 6(5), 100. https://doi.org/10.3390/ai6050100 Rafiq-uz-Zaman, M. (2022). Strategic upskilling: Fusing technical expertise with human capabilities. Journal of Business Insight and Innovation, 1(1), 76–86. https://doi.org/10.5281/zenodo.17766381 Rafiq-uz-Zaman, M. (2023). Bridging CPEC-driven industrial growth and skill-based education in Pakistan: A systematic review. Journal of Business Insight and Innovation, 2(1), 55–78. https://insightfuljournals.com/index.php/JBII/article/view/57 Rafiq-uz-Zaman, M. (2023). Redesign for 21st-century skills: Preparing learners for a rapidly changing workforce. Journal of Business Insight and Innovation, 1(2), 89–102. https://insightfuljournals.com/index.php/JBII/article/view/58 Rafiq-uz-Zaman, M. (2024). Leveraging skill development and STEAM innovation for business growth: A strategic framework for enhancing workforce performance in emerging markets. Journal of Business Insight and Innovation, 3(1), 48–63. https://insightfuljournals.com/index.php/JBII/article/view/55 Rafiq-uz-Zaman, M. (2025). Beyond the blackboards: Building a micro-edtech economy through teacher-led innovation in low-income schools. Journal of Business Insight and Innovation, 4(1), 46–52. https://doi.org/10.5281/zenodo.16875721 Rafiq-uz-Zaman, M. (2025). From chalkboards to competence: Rethinking skill-based education in Pakistan for a business-led innovation economy. International Journal of Academic Research for Humanities, 5(3), 1–13. https://doi.org/10.5281/zenodo.17112058 Rafiq-uz-Zaman, M. (2025). Use of artificial intelligence in school management: A contemporary need of school education system in Punjab (Pakistan). Journal of Asian Development Studies, 14(2), 1984–2009. https://doi.org/10.62345/jads.2025.14.2.56 Rafiq-uz-Zaman, M. (2025). Between adoption and ambiguity: Navigating the AI policy vacuum in Pakistani higher education. Research Journal for Social Affairs, 3(6), 877–885. https://doi.org/10.71317/RJSA.003.06.0523 Rafiq-uz-Zaman, M., Malik, N., & Bano, S. (2025). Learning to innovate: WhatsApp groups as grassroots innovation ecosystems among micro-entrepreneurs in emerging markets. Journal of Asian Development Studies, 14(1), 1854–1862. https://doi.org/10.62345/jads.2025.14.1.47 Raisch, S., & Krakowski, S. (2021). Artificial intelligence and management: The automation–augmentation paradox. Academy of Management Review, 46(1), 192–210. https://doi.org/10.5465/amr.2018.0072 Review of Managerial Science. (2026). Artificial intelligence technologies and entrepreneurship: A hybrid literature review. Advance online publication. https://doi.org/10.1007/s11846-025-00839-4 Siddiqui, D., Mumtaz, U., & Ahmad, N. (2024). Artificial intelligence in entrepreneurship: A bibliometric analysis of the literature. Journal of Global Entrepreneurship Research, 14(1), 1–27. https://doi.org/10.1007/s40497-024-00385-5 Sirait, M., Hidayat, R., & Nugroho, Y. (2025). Artificial intelligence, labor substitution, and human capital development in startups. Journal of Innovation & Knowledge, 10(2), 101430. https://doi.org/10.1016/j.jik.2024.101430 Twabu, J. (2025). The impact of artificial intelligence on product innovation in SMEs. Technovation, 129, 102874. https://doi.org/10.1016/j.technovation.2024.102874 Yesuf, Y., & Fields, Z. (2025). Artificial intelligence adoption as a driver of innovation and competitiveness in SMEs: A bibliometric and systematic review. F1000Research, 14, 1187. https://doi.org/10.12688/f1000research.171494.1 Zhao, X., Liu, Y., & Xu, H. (2023). Artificial intelligence adoption and innovation performance: Evidence from entrepreneurial firms. Technological Forecasting and Social Change, 189, 122361. https://doi.org/10.1016/j.techfore.2023.122361